Histological and immunohistochemical analysis of human periapical lesions: a study of TGF-β1 and CD68 markers - Nermeen AbuBakr; Geraldine M. Ahmed; Amany Hany Mohamed Kamel (BMC Oral Health)
Abstract Background Various inflammatory and anti-inflammatory mediators, along with diverse cell types, are implicated in the development and progression of periapical lesions. This work aimed to assess the immuno-expression of transforming growth factor-beta 1 (TGF-β1) and CD68 (a macrophage marker), elucidating their roles and potential correlations. Additionally, histological analysis was conducted to evaluate the intensity of inflammatory infiltrates in chronic periapical lesion samples. Methods Tissue samples from fifty individuals with chronic periapical lesions [25 radicular cysts (RCs) and 25 periapical granulomas (PGs)] were obtained, along with control samples from four healthy third molars’ dental pulp. Histological examination and inflammatory infiltrate categorization were performed. Immunohistochemical analysis of TGF-β1 and CD68 markers, along with morphometric assessment, were conducted. Results The control group displayed normal, inflammation-free pulp tissues, while intense inflammation was observed in PGs and RCs (Score 4 and 3, respectively) dominated by macrophages, plasma cells, and lymphocytes. Immunohistochemistry showed higher TGF-β1 and CD68 expression in PGs and RCs versus control (P < 0.001). Moreover, PGs exhibited greater TGF-β1 and CD68 expression than RCs (P < 0.001). However, a negative relationship was detected between the 2 markers (P < 0.05). Conclusions This study highlighted varying expressions of TGF-β1 and CD68 in PGs and RCs, indicating their potential roles in lesion pathology. However, a negative correlation between these markers was observed. Accordingly, their precise role in periapical lesion progression and repair requires further investigation.